Kajian Dampak Faktor Green Marketing pada Tindakan Pembelanjaan Produk Lampu Aromaterapi Nabila Art Gallery Sidoarjo - Ismail, Rizky Nurrochmad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to search solutions to a few of problems experienced by UKM Nabila Art Gallery: buying unregistered products, simple marketing management, and not using social media. Simultaneous data processing through a quantitative approach and a survey method processed through the SPSS application shows that three variables are known to had a consequence influence on purchasing decisions: green products, green advertising and green brands. Partially (separately) green products and green advertising have a significant effect on purchasing decisions. Green brands alone do not have a significant impact on purchasing decisions. Therefore, businesses should support three factors that influence their purchasing decisions: green products, green advertising and green brands, giving it a rating of 63.20%. The addition of the Green Price factor for the next study is expected to maximize results.